2021
DOI: 10.1145/3429446
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Network Approach to Predict Individuals’ Mental Health

Abstract: Depression and anxiety are critical public health issues affecting millions of people around the world. To identify individuals who are vulnerable to depression and anxiety, predictive models have been built that typically utilize data from one source. Unlike these traditional models, in this study, we leverage a rich heterogeneous dataset from the University of Notre Dame’s NetHealth study that collected individuals’ (student participants’) social interaction data via smartphones, health-related behavioral da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Mcpeak et al' s research on adolescent patients with mental illness also found that people with high menstrual quality have a tendency to develop spermatic diseases [ 4 ]. Related studies have found that adolescents with childhood trauma experience are more likely to have emotional and behavioral problems such as anxiety, suicidal ideation, drug abuse, self-harm, and aggressive behavior [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mcpeak et al' s research on adolescent patients with mental illness also found that people with high menstrual quality have a tendency to develop spermatic diseases [ 4 ]. Related studies have found that adolescents with childhood trauma experience are more likely to have emotional and behavioral problems such as anxiety, suicidal ideation, drug abuse, self-harm, and aggressive behavior [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm was proved to outperform the baseline through simulation experiments [6]. Liu et al modeled the collected Net Health data as HIN in order to identify individuals vulnerable to depression and anxiety, and then a novel way to redefine the problem of predicting individual mental health status, and finally modeled individual mental health prediction as a node classification in HIN of another problem type by evaluating four node features as proof-of-concept classifiers in the process of logistic regression [7]. Sharma et al implemented functional encryption of letters in UAV-assisted heterogeneous networks for dense urban areas to protect data from illegal intrusion; the main goal of this technique implementation is to provide proof-of-safe passage against illegal intrusion.…”
Section: Related Workmentioning
confidence: 99%
“…In Equation (7), η is the learning rate. ∂ is the number of iterations, and θ is the randomly selected pairs of nodes from the heterogeneous network.…”
Section: Heterogeneous Network Embedding Frameworkmentioning
confidence: 99%
“…Many scholars have proposed to use deep neural network models such as CNN [ 11 ] and Bi-LSTM [ 12 ] to analyze and train the influencing factors affecting students' affective cognition problems and establish analytical models to classify and predict students' affective cognition problems. In addition, the literature [ 13 ] and the literature [ 14 ] applied the massive data recorded by the relevant systems on campus to mine the behavioral data related to students' affective cognition. Meanwhile, artificial intelligence algorithms are used to intelligently identify students' abnormal behavior and construct early warning models.…”
Section: Introductionmentioning
confidence: 99%